2015
DOI: 10.1186/s12889-015-2343-8
|View full text |Cite
|
Sign up to set email alerts
|

Texting at the light and other forms of device distraction behind the wheel

Abstract: BackgroundCell phones are a well-known source of distraction for drivers, and owing to the proliferation of text messaging services, web browsers and interactive apps, modern devices provide ever-increasing temptation for drivers to take their eyes off the road. Although it is probably obvious that drivers’ manual engagement of a device while their vehicles are in motion is potentially dangerous, it may not be clear that such engagement when the vehicle is at rest (an activity broadly labeled “texting at the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…For example, if the motor task involves fine motor control of movements and high levels of concentration, even insignificant sensory stimuli can compromise the neural activation of the working muscles (see Bernstein & Bernstein 2015). Fortunately, the attentional system is trainable, and humans have developed psychological techniques that normally involve the control of physiological indices as a means by which to avoid the detrimental effects of task-irrelevant factors on task performance (Bernier et al 2011; Desbordes et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if the motor task involves fine motor control of movements and high levels of concentration, even insignificant sensory stimuli can compromise the neural activation of the working muscles (see Bernstein & Bernstein 2015). Fortunately, the attentional system is trainable, and humans have developed psychological techniques that normally involve the control of physiological indices as a means by which to avoid the detrimental effects of task-irrelevant factors on task performance (Bernier et al 2011; Desbordes et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study conducted in one intersection in Pennsylvania in 2014 of 2,000 observed drivers, found 3% of drivers in motion were texting or visibly manipulating handheld devices and 5% were engaged in handheld phone calls. Among the stopped drivers, 14.5% were texting and 6.3% were talking (Bernstein & Bernstein, 2015). Further work is necessary to describe the proportion of time individual drivers use their phone while the car is in motion.…”
Section: Incidence Of Cellphone Use While Driving In Adolescentsmentioning
confidence: 99%
“…Consistent with previous research (e.g., Bernstein & Bernstein, 2015), results of Study 1A found that many young drivers reported using their smartphone while stopped at traffic lights. While this situation was not specifically investigated beyond Study 1A, it, too, can result in the loss of situational awareness and a delayed response to a sudden change in road conditions, such as the traffic light turning green (Bernstein & Bernstein, 2015).…”
Section: Practical Implicationssupporting
confidence: 91%
“…For example, frequent users of mobile phones (many young people could be classified as frequent users) were less likely to perceive the risk of heavy traffic as preventing them from using their mobile phone while driving (K. M. White et al, 2012). A recent observational study reported five times the number of drivers (14.5%) were texting when stopped at a red traffic light compared to drivers in moving vehicles (Bernstein & Bernstein, 2015). While a driver may perceive that using their smartphone at a red light is less risky than in moving traffic, it can result in the loss of situational awareness and a delayed response to a sudden change in road conditions, such as the traffic light turning green (Bernstein & Bernstein, 2015).…”
Section: Critical Belief Possible Message Content and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation